We Reveal Ourselves to Ourselves: The New Communication Media in the Philippines - Pertierra, Raul (Social Science Diliman: A Philippine Journal of Society and Change, 2013)
The cellphone and the Internet are very signif icantly changing the communication landscape in the Philippines. Concomitantly, the new media are transforming social relationships in new and unexpected ways. With the new media, not only can Filipinos more easily communicate with their relatives and friends abroad; they also have new possibilities for revealing important aspects of self-identity. Mobiles are the most important new technology introduced in the Philippines and their effects far exceed most expectations. Even relationships with the recently dead are being affected by this technology. Moreover, the new media are also transforming older communication media, helping them penetrate and influence increasing aspects of everyday life. While the emancipatory possibilities of the new communication media are promising, new divisions and inequalities are also arising. Access to communication is emerging as one of the major sources of inequality. Keywords: New media, technology-mediated relationships, virtual reality, discursive intimacy, self and other